2013
DOI: 10.1007/s10753-013-9599-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Has Potent Anti-inflammatory Actions in a Mouse Model of Acute Lung Injury

Abstract: Septic shock is a systemic inflammatory response syndrome, and it is the leading cause of death in intensive care units. Mycophenolate mofetil (MMF) is an immunosuppressant that has been shown to be effective in the treatment of various inflammatory diseases. In this study, the anti-inflammatory effect of MMF in a mouse model of acute lung injury (ALI) induced by lipopolysaccharide (LPS) was evaluated. ALI was induced by intrapleural injection of LPS (250 ng/cavity). The leukocyte migration, exudation, myelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
3
0
1
Order By: Relevance
“…7,8 In the c-ART era, the prevalence of systolic dysfunction in HIV+ patients is estimated to be ≈8% and prevalence of clinical heart failure to be ≈3%. 15 In the current analysis, we found that the rates of CAV in HIV+ recipients up to 5 years of follow-up (KM estimate of 32.0%) were similar to the CAV rates (29.3%) observed in the overall HT population as per the recent International Society for Heart and Lung Transplantation report. 15 In the current analysis, we found that the rates of CAV in HIV+ recipients up to 5 years of follow-up (KM estimate of 32.0%) were similar to the CAV rates (29.3%) observed in the overall HT population as per the recent International Society for Heart and Lung Transplantation report.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…7,8 In the c-ART era, the prevalence of systolic dysfunction in HIV+ patients is estimated to be ≈8% and prevalence of clinical heart failure to be ≈3%. 15 In the current analysis, we found that the rates of CAV in HIV+ recipients up to 5 years of follow-up (KM estimate of 32.0%) were similar to the CAV rates (29.3%) observed in the overall HT population as per the recent International Society for Heart and Lung Transplantation report. 15 In the current analysis, we found that the rates of CAV in HIV+ recipients up to 5 years of follow-up (KM estimate of 32.0%) were similar to the CAV rates (29.3%) observed in the overall HT population as per the recent International Society for Heart and Lung Transplantation report.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, immunosuppressive medications have been shown to have potent anti-inflammatory properties as well. 15 In the current analysis, we found that the rates of CAV in HIV+ recipients up to 5 years of follow-up (KM estimate of 32.0%) were similar to the CAV rates (29.3%) observed in the overall…”
Section: Discussionsupporting
confidence: 79%
“…In congruence with the lower number of bacteria and improved lung morphology, the levels of the key cytokines tumor necrosis factor alpha (TNF-a) and interferon gamma (INF-g) were also significantly reduced (Figures S3B and S3C) concentration of the granulocyte marker enzyme myeloperoxidase (MPO) was diminished (p < 0.001), indicating reduced inflammation ( Figure S3D). It is likely that the decreased inflammatory parameters result not only indirectly from the reduced Ctr burden but also directly from the anti-inflammatory effect of MMF, e.g., via the reduction of rapidly proliferating B and T lymphocytes (Beduschi et al, 2013). However, the immunomodulatory effect of MMF, a well-tolerated drug used in long-term regimens for transplant and arthritis patients (Goldblum, 1993), does not necessarily diminish its potential value as an anti-infective against Ctr.…”
Section: Targeting Of Impdh Is Effective In Vivomentioning
confidence: 99%
“…It has been confirmed that intratracheal instillation of the endotoxin, lipopolysaccharide (LPS), can reproducibly induce ALI (7). LPS induces inflammatory cell infiltration into lung tissues, causing the release of proinflammatory cytokines, reactive oxygen species and chemotactic factors (8). These changes can cause lung edema, alveolar hemorrhage and substantial inflammation.…”
Section: Introductionmentioning
confidence: 99%